Optimalisasi Pengelolaan Laboratorium PGMI Sebagai Sumber Belajar IPA - Retno Wahyu (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2017)
Â Currently laboratory PGMI has not functioned optimally. Only IPA the most often use the laboratory to support the process learning. In management, there has been no guidelines for discharging PGMI laboratory. The purpose of this research to create the prototype of management guidelines laboratory PGMI as a source of learning IPA in the FITK IAIN Surakarta. This is a research and development study which comprises Borg and Gall steps: information collecting, planning, developing preliminary product, expertsâ€™ judgments, and revising the main product. This study has produced a prototype management guidelines PGMI laboratory of FITK IAIN Surakarta: (a) The average components of governance, documents, monitoring and evaluation possesses the criteria â€œimportantâ€ to raised in management guidelines PGMI laboratory, (b) this prototype has a good validity construct, (c) Have enough reliability levels with value r of 0.533.Keywords: management, PGMI laboratory